Metastases to nasal cavity and paranasal sinuses. Issue 12 (24th May 2016) - López, Fernando; Devaney, Kenneth O.; Hanna, Ehab Y.; Rinaldo, Alessandra; Ferlito, Alfio
Abstract: The sinonasal cavities are rare locations for metastases. Metastases to these locations are usually solitary and produce similar symptoms to those of a primary sinonasal tumor. Nasal obstruction and epistaxis are the most frequent symptoms. The maxillary sinus is most frequently involved. The most common primary tumor sites to spread to this region originate in the kidney, breast, thyroid, and prostate, although any malignancy could potentially lead to a metastasis to the paranasal sinuses. The patient's prognosis is usually poor because of the fact that the sinonasal metastasis is usually associated with widespread disseminated disease. In the majority of patients, palliative therapy is the only possible treatment option. Nevertheless, whenever possible, surgical excision either alone or combined with radiotherapy may be useful for palliation of symptoms and, rarely, to achieve prolonged survival. This review considers the most interesting cases reported in the literature that presents metastases to the sinonasal cavities. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1847–1854, 2016